A methods engineering study on Le Jean de Marithe and Francois Girbaud - Dimaya, Tisha Mae; Escabel, Yvette; Velasco, Julius (Diliman, Quezon City College of Engineering, 2003)
JVS Asia, Inc. is a company whose strength lies in its group of competent sales and administrative staff and professional managers, in its control of the inventory and importation process, in its superior merchandising skills, and in its excellent relations with the major shopping center operators. On this note, the company wanted to find out if there could be improvements made in one of the stores they handle, which is Le Jean de Marithe + Francois Girbaud. Thus, the need for Methods Engineering. Data was gathered through interviews with the Human Resource Department and Information Technology Group in the Girbaud Office, actual observations during store visits, and Job Analysis Questionnaires distributed to the personnel of the store. Systems documentation and analysis was done through employing the various tools and techniques of Methods Engineering. The group identified all problem areas observed using the Stream Diagnosis Diagram. The main problem areas were determined and these are : (1) no standard basis for number of workers, (2) unreconciled inventory system count versus actual count, (3) frequent substitution of Security Assistant that leads to the frequent hiring of a temporary Security Assistant and (4) Standard Opening Procedures not followed. It is the task of the group to come up with possible solutions to the aforementioned problems. At least two feasible solutions or alternatives for each problem area were then identified. These alternatives were then evaluated against must and want objectives. The risks and threats of these alternatives against existing conditions were also assessed. The alternatives which have more desirable consequences as well as satisfy the objectives were chosen as solutions. For chosen alternatives of the problem area of no standard basis of number of workers, the group suggested that work areas or areas of responsibility be assigned to the Fashion Consultants. The proposed number of workers is twelve during weekends including Fridays and eleven during weekdays. Five Fashion Consultants, two Cashiers, two Stock Custodians, one Store Supervisor and one Assistant Store Supervisor comprise the eleven workers during weekdays. One Fashion Consultant would be added for the weekends. The chosen alternatives for the problem area of unreconciled inventory system count versus actual count is to utilize the scanner of the store. Through the utilization of the scanner, human errors from the entering of barcodes would be eliminated. Even thought the store has a permanent Security Assistant, he is sometimes needed in the warehouse. This leads to the frequent substitution of the Security Assistant. The temporary Security Assistant has to be briefed and yet sometimes the temporary Security Assistant tends to do things his own way like in taking the traffic count. For this problem, the group chose the alternative of briefing duties and responsibilities of the temporary Security Assistant before he reports to the store. For the final problem, Standard Operating Procedures not followed, the group chose the alternative of applying a point system for wage incentives. Aside from the chosen alternatives for the problem areas, the group suggested two cost reduction plans. The first is to decrease the number of cashiers and to assign the bagging activity to the Fashion Consultant, while the second is to restructure the hiring process. The first cost reduction plan is based on the fourteen day work sampling study conducted by the group on the store. The findings of the work sampling study revealed that Fashion Consultants spend 6.47 percent or 32 minutes of their eight hour shift bagging merchandise which is not supposed to be done by them but by the Cashiers. In lieu of this occurrence, the group recommended that the number of Cashiers be decreased and that the bagging activity be assigned to the Fashion Consultants. The chosen alternatives are subject for implementation. Implementation plans and strategies were provided by the group. These plans may serve as a guide to the company in the implementation of the various changes brought about by the alternatives.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Le Jean de Marithe and Francois Girbaud; Clothing trade; Systems analysis